Secondary Myeloid Malignancy after Treatment of Acute Lymphoblastic Leukemia (ALL) (Hematology Meeting Reports, 2009)
Treatment of childhood acute lymphoblastic leukemia (ALL) has made tremendous strides over the past 20 years, but has been complicated by the induction of secondary tumors after some regimens. The cumulative incidence of therapy-related myeloid leukemia and myelodysplastic syndrome (referred to collectively as t-ML) varies widely among treatment protocols, from 1% to 12%.